A review of mineral associations and paragenetic groups of secondary minerals of the Jachymov (Joachimsthal) ore district - Ondrus,P.; Veselovsky,F.; Hlousek,J. (Journal of the Czech Geological Society, 1997)
This paper presents information on relations between physical-chemical properties and genetic features for two hundred and seven secondary minerals and thirty natural phases newly discovered in the Jachymov ore district. Eight distinct paragenetic groups are described and discussed with respect to formation conditions of the secondary minerals in the Jachymov ore district.
Keywords: mineral associations; paragenetic groups; secondary minerals; Jachymov